Rola kobiety w okresie prenatalnym i pierwszych dniach życia dziecka w świetle XVIII-wiecznego poradnika Józefa Legowicza - Ziomek, Patrycja (Biuletyn Historii Wychowania, 2016)
The author of the article presents how eighteenth-century writer Józef Legowicz sees the issue of motherhood. Józef Legowicz was a priest and a doctor of theology. He was a parson in Korkożyszki, a small village in Lithuania. He published 18 works, one of which was the guidebook Wedlock. He tried to show his parishioners the best way to achieve a harmonious marriage and raise children as good Christians. This guidebook is a valuable source of information about mother- and fatherhood in 18th Century Poland. The main task of this article is to show the unique role of women in the early stages of a child’s life.